2022
DOI: 10.3389/fphys.2022.821199
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-Running Facilitates Phase Advances in Locomotor and Peripheral Circadian Rhythm in Social Jet Lag Model Mice

Abstract: The circadian clock maintains our health by controlling physiological functions. Social jet lag is one factor that can disrupt the body clock. This is caused by the difference in sleeping hours between weekdays when we live according to social time and holidays when we live according to our body clock. The body clock can be altered by exercise, nutrition, and stress, and several studies have reported that these factors can be used to improve a disturbed body clock. Here we focused on exercise and examined whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Similar increases in Per2 expression in skeletal muscle have also been observed after both acute aerobic and resistance exercise 45 . Using the Per2 luciferase reporter mouse, studies have also shown the phase shifting ability of exercise in peripheral tissues 40 , 46 , 47 , however, this technique has not been used in the heart. More studies into how exercise affects the cardiomyocyte circadian clock are needed to better understand its influence.…”
Section: Discussionmentioning
confidence: 99%
“…Similar increases in Per2 expression in skeletal muscle have also been observed after both acute aerobic and resistance exercise 45 . Using the Per2 luciferase reporter mouse, studies have also shown the phase shifting ability of exercise in peripheral tissues 40 , 46 , 47 , however, this technique has not been used in the heart. More studies into how exercise affects the cardiomyocyte circadian clock are needed to better understand its influence.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions mimicking SJL, the time of light going on and off was delayed on weekends for 6 h, and thereafter from Monday, normal LD conditions were maintained (light: dark = 12:12) ( Figure 1 ). We established and used the SJL mice model in previous studies ( 26 , 27 ), and, in this study, we aimed to evaluate the way to reduce the SJL using this SJL mimicking model.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, in mice, LAN not only disrupts circadian rhythms, but also alters metabolism, immune function, stress, anxiety-like behavior, and mood-related behaviors ( Fonken et al, 2010 ; Bedrosian et al, 2013 ; Fonken et al, 2013 ; Fonken and Nelson, 2014 ; Russart and Nelson, 2018 ; Walker et al, 2020a , Walker et al, 2020b ; Bumgarner and Nelson, 2021 , Walker et al, 2021 ). However, more translational models of circadian rhythm disruption such as LAN, or even social jet lag and shift work ( Wittmann et al, 2006 ; Barclay et al, 2012 ; Opperhuizen et al, 2015 ; Haraguchi et al, 2021 ; Oneda et al, 2022 ), have been heavily underutilized in the study of circadian rhythm disruption and drug abuse, especially in the context of VTA and NAc circadian function. Future studies would benefit from utilizing these models to understand how unhealthy light practices (e.g., LAN, social jet lag, night shift work, etc.)…”
Section: Implications For Reward and Substance Abusementioning
confidence: 99%